2006
DOI: 10.1021/ol061070z
|View full text |Cite
|
Sign up to set email alerts
|

Application of Palladium-Catalyzed Allylic Arylation to the Synthesis of a (±)-7-Deoxypancratistatin Analogue

Abstract: Palladium-catalyzed coupling of an aryl siloxane and an allylic carbonate proceeded in good yield to give an adduct that was converted to an analogue of (+/-)-7-deoxypancratistatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 34 publications
0
9
0
4
Order By: Relevance
“…Other routes to the amaryllidacea alkaloids and their core structure have been reported that utilize similar nitrosocarbonyl HDA reactions. [33,[161][162][163][164][165] The total synthesis of the related fused polycyclic piperidine-containing alkaloid (+)-streptazolin (172) has also been reported by the Miller research group (Scheme 31). [166,167] The chiral cyclopentenol (À)-84 was converted into intermediate 170, which underwent an intramolecular aldol condensation to furnish compound 171.…”
Section: Amaryllidacea Alkaloids and Related Structuresmentioning
confidence: 94%
“…Other routes to the amaryllidacea alkaloids and their core structure have been reported that utilize similar nitrosocarbonyl HDA reactions. [33,[161][162][163][164][165] The total synthesis of the related fused polycyclic piperidine-containing alkaloid (+)-streptazolin (172) has also been reported by the Miller research group (Scheme 31). [166,167] The chiral cyclopentenol (À)-84 was converted into intermediate 170, which underwent an intramolecular aldol condensation to furnish compound 171.…”
Section: Amaryllidacea Alkaloids and Related Structuresmentioning
confidence: 94%
“…Nach einem erfolglosen Versuch der Synthese von (±)‐7‐Desoxypancratistatin ( 2 ) entwickelte DeShong zunächst eine Synthese von (±)‐3,4,7‐Tridesoxypancratistatin ( 315 ), bevor er 2012 die gelungene Synthese von (±)‐7‐Desoxypancratistatin ( 2 ) veröffentlichte . Die grundlegende Strategie der Synthese ist die gleiche wie die in Abschnitt 2.2.3 erörterte (DeShong, 2012).…”
Section: Nichtnatürliche Analoga Von Amaryllidaceae‐ Alkaloidenunclassified
“… Vom Ethylcarbamat 312 ausgehende Synthese von (±)‐3,4,7‐Tridesoxypancratistatin ( 315 ) durch DeShong …”
Section: Nichtnatürliche Analoga Von Amaryllidaceae‐ Alkaloidenunclassified
See 1 more Smart Citation
“…Auch andere Wege zu den Amaryllidacea-Alkaloiden und ihrer Kernstruktur wurden beschrieben, die auf eine ganz ähnliche Weise Nitrosocarbonyl-HDA-Reaktionen verwenden. [33,[161][162][163][164][165] Die Totalsynthese des verwandten kondensierten polycyclischen piperidinhaltigen Alkaloids (+)-Streptazolin (172) wurde ebenfalls durch den Arbeitskreis von Miller beschrieben (Schema 31). [166,167] Das chirale Cyclopentenol (À)-84 wurde in das Intermediat 170 umgewandelt, das über eine intramolekulare Aldolkondensation zu 171 reagierte.…”
Section: Amaryllidacea-alkaloide Und Verwandte Strukturenunclassified